2015
DOI: 10.1108/jd-03-2014-0049
|View full text |Cite
|
Sign up to set email alerts
|

As simple as that?: tween credibility assessment in a complex online world

Abstract: Purpose -The purpose of this paper is to focus on disadvantaged tweens' (ages 11 through 13) strategies for making predictive and evaluative judgments of the credibility of health information online. More specifically, this paper identifies the features of Google search results pages and web sites that signal credibility (or lack thereof) to this population and the reasons behind their perceptions. Design/methodology/approach -The authors employed an ethnographic approach (using various types of data collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 38 publications
1
42
0
2
Order By: Relevance
“…In recent years, there has been a growing number of studies that investigate how youth interact with computing systems and digital media, particularly how they seek information on the open Web, assess the credibility of information, and/or confirm/reject their biases as they decide which information to use (e.g., Agosto 2002a, b;Eastin 2008;Flanagin and Metzger 2008;Francke et al 2011;Gasser et al 2012;Hansen et al 2003;Shenton and Dixon 2004;St. Jean et al 2015;Subramaniam et al 2015a, b). Future research is needed to explore the existence/nature of the relationship between young people's mental models of search engines and the heuristics they rely on when interacting with them and assessing the credibility of online information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there has been a growing number of studies that investigate how youth interact with computing systems and digital media, particularly how they seek information on the open Web, assess the credibility of information, and/or confirm/reject their biases as they decide which information to use (e.g., Agosto 2002a, b;Eastin 2008;Flanagin and Metzger 2008;Francke et al 2011;Gasser et al 2012;Hansen et al 2003;Shenton and Dixon 2004;St. Jean et al 2015;Subramaniam et al 2015a, b). Future research is needed to explore the existence/nature of the relationship between young people's mental models of search engines and the heuristics they rely on when interacting with them and assessing the credibility of online information.…”
Section: Resultsmentioning
confidence: 99%
“…This provides an impetus for search engine developers to more clearly and more readily convey to users how search results were selected for inclusion in the search results list and how they were sorted in order to better educate users (in this case, youth) on how they can effectively and efficiently assess the credibility of search results, given the nature of their queries. Previous studies (e.g., Eastin 2008;Flanagin and Metzger 2008;Subramaniam et al 2015a) have shown that youth have tremendous difficulty in assessing the credibility of search results and of the information they obtain online. Thus, comprehending how the search engine generated the results list may actually help youth to make wise decisions in their selection of information and enable them to form effective heuristics for assessing the credibility of open Web information sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent focus has been on youth health related information seeking (i.e. Kodama, Jean, Subramaniam, & Taylor, 2017;Subramaniam et al, 2015) where young people's digital literacy and their information-credibility and quality decisions have been explored. Similarly recent investigations explored children's mental models of information seeking interfaces and computers (Robertson, Manches, & Pain, 2017;Taylor, 2018).…”
Section: Children's Information Seeking and Usementioning
confidence: 99%
“…Even assuming that youth have access to computers and the ability to search for and evaluate health information, they may lack the motivation to do so. Youth may not conduct a search if they have no personal interest in a topic [38,39] or if they feel they already know the answer to a health-related question [40]. Similarly, they may not engage in a health-related information search due to a lack of self-efficacy in this area, as determined by associated factors such as optimism, persistence, and goal-orientedness [41,42].…”
Section: Introductionmentioning
confidence: 99%